2019
DOI: 10.1038/s41565-018-0336-3
|View full text |Cite|
|
Sign up to set email alerts
|

Binding to nanopatterned antigens is dominated by the spatial tolerance of antibodies

Abstract: Although repetitive patterns of antigens are crucial for certain immune responses, an understanding of how antibodies bind and dynamically interact with various spatial arrangements of molecules is lacking. Hence, we introduce a new method where molecularly precise nanoscale patterns of antigens are displayed using DNA origami and immobilized in a surface plasmon resonance (SPR) setup. Using antibodies with identical antigen binding domains, we find that all subclasses and isotypes studied, bind bivalently to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
149
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 62 publications
6
149
5
1
Order By: Relevance
“…We hypothesize that the observed decrease in signaling response of B cells to dimers with short inter-antigen distances is due to a bivalency effect, whereby single immunoglobulins are binding to both eOD sites when inter-antigen spacing is below ~28 nm, thereby resulting in engagement of only single BCRs. This hypothesis would further underline the importance of coordination between multiple antigen receptors for efficient receptor signaling, as shown previously using programmed DNA assemblies 15,16 . Affinity is an important determination of BCR responses 33,34 , where it is important to note here that the affinity between germ-line VRCO1 and eOD-GT8 is in the sub-nanomolar range, which places this system in the regime of mature BCR antigen affinities rather than naïve affinities.…”
Section: Main Textsupporting
confidence: 59%
See 1 more Smart Citation
“…We hypothesize that the observed decrease in signaling response of B cells to dimers with short inter-antigen distances is due to a bivalency effect, whereby single immunoglobulins are binding to both eOD sites when inter-antigen spacing is below ~28 nm, thereby resulting in engagement of only single BCRs. This hypothesis would further underline the importance of coordination between multiple antigen receptors for efficient receptor signaling, as shown previously using programmed DNA assemblies 15,16 . Affinity is an important determination of BCR responses 33,34 , where it is important to note here that the affinity between germ-line VRCO1 and eOD-GT8 is in the sub-nanomolar range, which places this system in the regime of mature BCR antigen affinities rather than naïve affinities.…”
Section: Main Textsupporting
confidence: 59%
“…To date, studies exploring the effect of antigen organization on B cell triggering have generally employed protein, polymer, or particle scaffolds that only allowed limited variation of spatial parameters, or provided only statistical control over the numbers and locations of antigens 2,3,[9][10][11][12] . In order to independently probe the relative roles of immunogen valency and spacing on BCR activation, here we used scaffolded DNA origami NPs 13,14 to display discrete antigen copy numbers with controlled inter-antigen spacings on the scale of an individual virus-like NP 15,16 . As a model antigen, we employed an HIV germline-targeting gp120 protein, the engineered outer domain eOD-GT8.…”
Section: Main Textmentioning
confidence: 99%
“…Furthermore, isolated TCR pairs enforced by divalent DNA origami platforms were still signalingcompetent: platforms featuring scFVs at 10 and 20 nm distance and thus closely mimicking IgG antibodies 31 were most potent. Given the lateral dimensions of the TCR-CD3 complex with a diameter of about 10 nm 32 , we consider it likely that close apposition of two TCR-CD3 complexes but not necessarily their physical association is required for efficient initiation of intracellular signaling.…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of this manuscript, two elegant studies appeared that also aimed at describing the spatial dependence of avidity. Using DNA origami to control the spacing of epitopes, 28 Shaw et al found that maximal avidity occurred at a spacing of 16 nm, and decreased ten-fold at a spacing of 17 nm. This study also suggested that the spatial dependence of avidity depended strongly on the strength of the monovalent affinity.…”
Section: Introductionmentioning
confidence: 99%
“…This study also suggested that the spatial dependence of avidity depended strongly on the strength of the monovalent affinity. 28 At a monovalent KD ~3 µM, bivalent binding and avidity enhancement was only observed at the optimal epitope spacing, whereas avidity was observed at a broad range of spacings at a monovalent KD ~30 nM. Similarly, Zhang et al used triangular DNA nanostructures and highspeed AFM to measure multivalent binding to epitopes spaced from 3 to 20 nm.…”
Section: Introductionmentioning
confidence: 99%